Linguistic Strategies and Psychological Empowerment in Female Leaders: A Discourse Analysis Across Male-Dominated Fields (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examined how female leaders in male-dominated sectors including STEM, politics, and finance used language to assert psychological agency and construct leadership identity. Despite extensive documentation of structural barriers to women’s advancement in these fields, the psycholinguistic mechanisms underlying empowerment remained insufficiently explored. Drawing on self-determination theory and social role theory, the study analysed publicly available transcripts of speeches and interviews from 15 prominent women leaders aged 35 to 65 who held positions of formal authority. A qualitative discourse analysis was conducted, focusing on linguistic features such as pronoun usage, modality, and metaphor. The analysis identified recurring strategies that conveyed both assertiveness and relationality, including the use of collective pronouns (e.g., “we”) to promote inclusivity, modal verbs (e.g., “must,” “can”) to express agency and obligation, and metaphors framing leadership as guidance, innovation, or transformation. Political leaders frequently used self-referential language to assert authority, while leaders in STEM favoured evidential and technical language to establish credibility. These linguistic patterns were interpreted as context-sensitive strategies employed to navigate gendered expectations while maintaining psychological empowerment. The findings highlighted language as a critical tool for negotiating identity, asserting control, and reinforcing leadership legitimacy in professional spaces historically shaped by masculine norms. This research contributed to the understanding of how discourse operates as both a reflection and facilitator of psychological empowerment among women in leadership.